Synaptic Plasticity After Focal Cerebral Ischemia Was Attenuated by Gap26 but Enhanced by GAP-134 - Yang, Kailing; Zhou, Ying; Zhou, Lequan; Yan, Fuman; Guan, Li; Liu, Haimei; Liu, Wei (Frontiers in Neurology, 2020)
Objective: Synaptic plasticity is critical for neurorehabilitation after focal cerebral ischemia. Connexin 43 (Cx43), the main component of gap junction, has been shown to be pivotal for synaptic plasticity. The objective of this study was to investigate the role of Cx43 inhibitor (Gap26) and gap junction modifier (GAP-134) in neurorehabilitation and to study their contribution to synaptic plasticity after focal ischemia. Methods: Time course expression of both total and phosphorylated Cx43 (p-Cx43) were detected by western blotting at 3 d, 7 d, 14 d after focal ischemia. Gap26 and GAP-134 were administered starting from 3 d post focal ischemia. Neurological performances were evaluated by balance beam walking test and Y-maze test at 1 d, 3 d, and 7 d. Golgi staining and transmission electron microscope (TEM) detection were conducted at 7 d for observing dendritic spine numbers and synaptic ultra-structure respectively. Immunofluorescent staining was used at 7 d for detection of synaptic plasticity markers, including synaptophysin (SYN) and growth associated protein-43 (GAP-43). Results: Expression levels of both total Cx43 and p-Cx43 were increased after focal cerebral ischemia, peaking at 7 d. Compared with MCAO group, Gap26 worsened neurological behavior and decreased dendritic spine number while GAP-134 improved neurobehavior and increased number of dendritic spines. Moreover, Gap26 further destroyed synaptic structure, concomitant with down-regulated SYN and GAP-43, whereas GAP-134 alleviated synaptic destruction and up-regulated SYN and GAP-43. Conclusion: These findings suggested that Cx43 or gap junction was involved in synaptic plasticity, thereby promoting neural recovery after ischemic stroke. Treatments enhancing gap junctions may be potential promising therapeutic measures for neurorehabilitation after ischemic stroke.